Strategie finansowania przedsiębiorstwa a kształtowanie struktury kapitału - Dylewski, Marek (Corporate financial strategies in the context of capital structure, 2006)
The paper presents the problems of choosing and monitoring capital structure in general and in comparison with company assets. Taking under consideration a balance sheet as the simplest method of creating financial strategy there are shown three forms of different relations among assets and liabilities in a company balance sheet.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 105-111